2014
DOI: 10.3390/molecules191016402
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Development of EST-SSR Markers Derived from Transcriptome of Yellow Catfish

Abstract: Yellow catfish (Pelteobagrus fulvidraco) is one of the most important freshwater fish due to its delicious flesh and high nutritional value. However, lack of sufficient simple sequence repeat (SSR) markers has hampered the progress of genetic selection breeding and molecular research for yellow catfish. To this end, we aimed to develop and characterize polymorphic expressed sequence tag (EST)-SSRs from the 454 pyrosequencing transcriptome of yellow catfish. Totally, 82,794 potential EST-SSR markers were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 20 publications
2
20
2
Order By: Relevance
“…Among its numerous applications, it has significantly advanced the development of transcriptomederived SSR markers in a number of plant and animal species, including tree peony and yellow catfish (Wu et al, 2014;Zhang et al, 2014). In this study, using the Illumina Hiseq-2000 platform, we were able to analyze transcriptome ESTs, generate 142,950 contigs, and design a higher number of potential SSR primers (12,208) compared to previous studies of D. involucrata (Du et al, 2012;Li et al, 2012b;Tao et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Among its numerous applications, it has significantly advanced the development of transcriptomederived SSR markers in a number of plant and animal species, including tree peony and yellow catfish (Wu et al, 2014;Zhang et al, 2014). In this study, using the Illumina Hiseq-2000 platform, we were able to analyze transcriptome ESTs, generate 142,950 contigs, and design a higher number of potential SSR primers (12,208) compared to previous studies of D. involucrata (Du et al, 2012;Li et al, 2012b;Tao et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Eighteen male and eighteen female breeding fishes (1 year old) were selected from the cross-hybridization offspring between one cultured and four wild populations as previously described (Zhang et al 2014). Eighteen full-sib families (named P1 to P18) were obtained by artificial insemination and had been fed with artemia for 3 weeks.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The offspring from the 18 crosses, and their parents were genotyped with seven SSRs (H20, H147, H152, H159, H160, H259, H260) developed previously (Zhang et al 2014) and two new SSRs (H273, H276) as shown in Table 1. The primer pairs of the microsatellite markers were designed by using the software Primer Premier 5.0.…”
Section: Dna Extraction and Genotyping Of Microsatellitesmentioning
confidence: 99%
See 2 more Smart Citations